Penatalaksanaan fraktur mandibula pada anak menggunakan teknik circumferential wiring dengan Gunning splint Management of mandibular fracture in children using circumferential technique with Gunning splint - S. Haryoseno; Abel Tasman Yuza; Bambang A. Sulthana (DiscoverSys Inc., 2012)
Fractures of the mandible in children most commonly occur in the condyle and angulus. Circumferential wiring andGunning splint as a supporting tool to strengthen the fixation of the lower jaw. This case reported a 7 year-old-boywho had fracture of his right mandibular corpus. At the time of surgery, it was applied mini plate 5 holes and 4screws on the right mandibular corpus with the using of circumferential wiring on the right and left mandibularcorpus and symphysis, with Gunning splints. The patient was in good condition after surgery without complications